SOCIALLY-PHILOSOPHICAL ASPECT INVESTIGATION OF LIBRARY FUNCTION FOR INFORMATION SOCIETY - Азнакаєва, Е. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The socially-philosophical judgement of library for а information society is presented in article.